Kompetencje samorządu terytorialnego w zakresie ochrony i kształtowania środowiska - Ciechanowicz, Janina (Wydział Prawa i Administracji UAM, 1991)
The issues of natural environment protection may be divided into three groups: local, regional and international ones. The powers of communal authorities extend to all public aspects, including the environment protection, connected with the satisfaction of collective needs of the local population. Such tasks belong to the category of so-called commune's own tasks. The provisions of substantive administrative law determine the scope and subject-matter of commune's powers. A separate category of tasks from so-called delegated tasks, belonging until recently to the competence of national councils and the organs of state administration. A commune may also carry out other delegated tasks, if a necessary agreement with the organs of governmet administration has been reached. Recent amendments of the Act on Environmental Protection have vested many powers in the organs of government administration and the organs of a commune. It schould be stressed that now a commune has exclusive powers to adopt zoning plans. Such plans are the basic legal instrument of environmental protection. Great prospects for the efficient approach to the problems of environmental protection offers the possibility of inter-communal cooperation of communes. Intercommunal unions and agreements established to fight water pollution of the Vistula and the Odra rivers, or to reduce air pollution would be the optimum way of exploitingthe powers of self-government.
The powers of territorial self-government in the sphere of natural environment protection and development